A novel current-mode temperature-insensitive APF using a single CCCII+2 with grounded capacitor - Kaewdang, Khanittha; Kumwachara, Kiattisak; Surakampontorn, Wanlop (My University, 2016)
A novel first-order all-pass filter (APF) using a single positive second-generation current conveyor of current gain equal to 2 (named as CCII+2), one grounded capacitor and one resistor is proposed. From the proposed CCII+2 based filter, by replacing the CCII+2 and the resistor with a positive second-generation current-controlled conveyor of current gain equal to 2 (named as CCCII+2), a new filter which requires only a single CCCII+2 and one grounded capacitor is achieved. In order to operate in current-mode with temperature insensitive, a temperature compensation technique for the CCCII is also proposed. The experimental and PSPICE simulation results found in a good agreement with theoretical analysis are included.
Keywords: All pass filter; CCCII; COI; Current mode